Fc gamma RI and Fc gamma RIII on polymorphonuclear leucocytes in cord blood. Issue 1 (January 1994) - Takahashi, N; Nishida, H; Kuratsuji, T
Abstract : Fc gamma RI and Fc gamma RIII expression on polymorphonuclear leucocytes in cord blood from seven normal infants was investigated by flow cytometry. Fc gamma R expression on fresh polymorphonuclear leucocytes in whole blood samples and in blood samples incubated with or without interferon gamma (IFN-gamma) for 48 hours was also studied. The percentage of Fc gamma RIII positive polymorphonuclear leucocytes in cord blood (73.3%) was significantly lower than that in adult controls (95.9%). The mean fluorescence intensity of Fc gamma RIII was significantly increased on cord polymorphonuclear leucocytes by the incubation with IFN-gamma. Fresh cord polymorphonuclear leucocytes expressed only a small amount of Fc gamma RI as adult polymorphonuclear leucocytes. The percentage of Fc gamma RI positive polymorphonuclear leucocytes induced with IFN-gamma was significantly higher in cord blood (62.3%) than in adult controls (30.3%). It is possible that decreased expression of Fc gamma RIII is a factor in the susceptibility of newborns to infection. High expression of Fc gamma RI stimulated with IFN-gamma in neonates could have a compensatory role against decreased immunological function.